2008
DOI: 10.1007/s11103-008-9409-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of lysine catabolism in maize kernels

Abstract: In plants, lysine catabolism is thought to be controlled by a bifunctional enzyme, lysine ketoglutarate reductase/saccharopine dehydrogenase (LKR/SDH). Lysine is converted to saccharopine, through condensation with alpha-ketoglutarate, by LKR, and subsequently to glutamate and alpha-aminoadipate-delta-semialdehyde by SDH. To investigate lysine catabolism in maize kernels, we generated transgenic plants with suppressed LKR/SDH activity in either endosperm or embryo. We found that the suppression of LKR/SDH in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…In addition, numerous approaches have been taken to boost the Lys content in plants (Azevedo and Lea, 2001;Galili et al, 2001;Ufaz and Galili, 2008), and for this reason, the degradative pathway has also been targeted. In one such strategy, a series of transgenic maize (Zea mays) plants overaccumulating Lys were produced using distinct strategies, including an endosperm-specific RNA interference suppression of LKR/ SDH (Houmard et al, 2007;Frizzi et al, 2008;Reyes et al, 2009). Most approaches that led to accumulation of Lys also led to a concomitant degradation of Lys, resulting in the formation of saccharopine and a-aminoadipate d-semialdehyde (Falco et al, 1995;Houmard et al, 2007;Frizzi et al, 2008;Azevedo and Arruda, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous approaches have been taken to boost the Lys content in plants (Azevedo and Lea, 2001;Galili et al, 2001;Ufaz and Galili, 2008), and for this reason, the degradative pathway has also been targeted. In one such strategy, a series of transgenic maize (Zea mays) plants overaccumulating Lys were produced using distinct strategies, including an endosperm-specific RNA interference suppression of LKR/ SDH (Houmard et al, 2007;Frizzi et al, 2008;Reyes et al, 2009). Most approaches that led to accumulation of Lys also led to a concomitant degradation of Lys, resulting in the formation of saccharopine and a-aminoadipate d-semialdehyde (Falco et al, 1995;Houmard et al, 2007;Frizzi et al, 2008;Azevedo and Arruda, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The combined approach of deregulating lysine synthesis and suppressing its catabolism was successful with as much as 4000 ppm free lysine accumulated in maize seeds. Reyes et al (2009) combined endospermspecific suppression of maize LKR/SDH with embryo-specific suppression of the gene, which resulted in a synergistic increase in maize seed free lysine content.…”
Section: Protein Modificationmentioning
confidence: 99%
“…These experiments showed that transgenic approaches, in addition to investigating relationships between zein synthesis and opaque endosperm, could be useful to increase kernel lysine content. Similarly, Reyes et al (2008), using RNAi, have produced transgenic maize lines that had LKR/SDH suppressed in the embryo, endosperm or both. These authors noted a synergist increase in free lysine content in the mature kernel when LKR/SDH was suppressed in both embryo and endosperm; these results have also suggested new insights into how free lysine level is regulated and distributed in developing grains.…”
Section: New Strategies For Creating Variationmentioning
confidence: 99%